SORPTION ISOTHERM, PROXIMATE COMPOSITION AND SENSORY EVALUATIONS OF OVEN DRIED AND FRIED CHEESE PRODUCTS FROM LOCAL SOFT CHEESE - Nathaniel O. Alamuoye, Oluwatoyin F. Alamuoye, Lawrence K. Otitoju, (EPRA International Journal of Research and Development (IJRD), 2024)
In this study, the sorption isotherm, proximate composition and sensory characteristics of oven dried and fried cheese were investigated. The understanding of the moisture sorption properties, nutrient composition and sensory properties of the oven dried and fried cheese can help quality, shelf-life prediction and overall acceptance. The experimental methodology for this study followed a standard procedure to determine the sorption isotherm of oven-dried and fried cheese samples. First, the raw milk samples were obtained from white Fulani cows at the Teaching and Research Farm, Ekiti State, University, Ado-Ekiti, Nigeria and processed into cheese. The cheese was divided into two portions: one group was oven-dried at 50 0C for 16 hours, while the other group was fried in pre-heated edible canola to internal temperature of 68oC. Sorption parameters, proximate and sensory characteristics were carried out according to standard methods. This study revealed that the monolayer moisture was higher in fried cheese than oven dried cheese. Oven-dried cheese had 0.299 water activity and 21.26 monolayer moisture while fried cheese had higher water activity of 0.32 and monolayer moisture of 29.67. Fitness of curve (R2) of 0.731 0.903 were computed for oven-dried and fried cheese. The results of proximate composition and sensory characteristics showed that processing methods influenced the sensorial properties and nutritional composition of oven-dried and fried cheese. In conclusion, oven-dried cheese can be predicted to be more stable than fried cheese.